Proposed upgrading of the ground floor of Perpustakaan Raja Tun Uda for Majlis Bandaraya Shah Alam at Persiaran Bandaraya, 40572 Shah Alam, Selangor Darul Ehsan / Muhammad Danial Ismail - Ismail, Muhammad Danial (Faculty of Architecture, Planning and Surveying, 2010)
The final project for the final year students in Interior Architecture is based on all the knowledge gained from all the past semesters from semester one till semester five. All the knowledge that has been learnt from these semesters will be put to the test by self proposing a final project based on real life factors such as the project itself, the client, the site and the budget. The chosen project will then go through several analysis and design processes before finally confirming the final design. The project chosen must have general and design issues related to them in order for it to be a visible project. Among the things that has been discovered is that the library is facing design problems such as the planning which leads to the traffic flow disorder in the building. This means that the existing design has failed and needs to be upgraded. Other issues discovered are things such as the image of the library is outdated which contributes to the main factor of the decreasing numbers of visitors to the library. These issues will then be solved by the designers design after analyzing all the details needed before starting the design process. In this thesis, the project that I have proposed is the project of upgrading the ground floor of Perpustakaan Raja Tun Uda library for Majlis Bandaraya Shah Alam at Persiaran Bandaraya 40572 Shah Alam Selengor. The project is funded by the client, MBSA itself or also known as the local state authority. The upgrading process of the project consists of the concept, image, planning and material & finishes. The concept that I have chosen for this project is ‘Powering Future Generations’ which means attracting more youth and the public to the library by upgrading the design to be more attractive thus generating the youth and the public to be more intelligent and knowledgeable. The image that I will apply in the design is hi-tech plus modern image which has the characteristics of wide open spaces, space frames, glass walls, architectural cladding, clean edges and more. The planning on the other hand must comply directly to the concept itself and at the same time applying the image that has been proposed.